Geoheritage 3. Attracting Students to the Earth Sciences: An Example of Individual and Collective Outreach Efforts by Industry, Academia and Secondary Education - Bank, Charly; Jackson, Deryk; Hymers, Lesley (Geoscience Canada, 2009)
Too few Canadian high-school students are pursuing post-secondary studies and career opportunities in the earth sciences. Given Canada’s wealth of renewable and non-renewable resources and their importance to society, it is imperative that students become literate in the earth sciences, and that they are encouraged to pursue career opportunities in the many fields that constitute the earth sciences. To achieve these goals, a number of out-reach efforts by members of industry, academia and secondary education have been initiated. We outline here an example of our own collaboration in one such program directed not only at students, but also at primary and secondary teachers, university faculty, industry representatives and government officials. Our program has achieved significant results, and so will continue. Others interested in increasing the profile of the earth sciences are encouraged to explore such new out-reach approaches. SOMMAIRE Trop peu d’élèves des écoles secondaires au Canada poursuivent des études en sciences de la Terre et choisissent d’y faire carrière. Étant donné la richesse du Canada en ressources renouvelables et non-renouvelables et leurs importances pour le bien commun, il est absolument essentiel que les élèves acquièrent des connaissances de base en sciences de la Terre et soit encourager à embrasser des carrières dans l’une des nombreuses spécialités du champ des sciences de la Terre. Pour y arriver, un certain nombre d’initiatives de sensibilisation ont été lancées par des membres du secteur industriel, du monde universitaire, et de l’éducation secondaire. Nous décrivons brièvement ci-dessous notre collaboration dans le cadre d’un programme du genre visant non seulement les élèves, mais aussi les enseignants des écoles primaires et secondaires, les membres du corps professoral des universités, les représentants du secteur industriel et ceux des gouvernements. Notre programme a connu des succès importants, et donc il sera maintenu. Nous incitons toute personne intéressée à promouvoir l’image des sciences de la Terre à considérer de telles approches nouvelles.